Analisis Normatif Terhadap Pertanggung Jawaban Pidana Korporasi Dalam Kejahatan Ekonomi Di Sektor Keuangan - Dermawan, Rian Rizky; Fardiansyah, Ahmad Irzal; Tamza, Fristia Berdian (Universitas Sang Bumi Ruwa Jurai, 2025)
Economic crimes committed by corporations in the financial sector are an increasingly complex phenomenon in the era of globalization. These crimes not only result in financial losses but also threaten economic stability and public trust. This research uses a normative juridical method with a statutory, conceptual, and case-based approach. The results indicate that corporate criminal liability for economic crimes still faces implementation challenges due to weak legal instruments and difficulties in providing evidence. Law Number 7 of 1992 in conjunction with Law Number 10 of 1998 concerning Banking, and Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering regulate the precautionary principle, but have not effectively ensnared corporate entities as subjects of criminal law. Therefore, regulatory harmonization and increased effectiveness of law enforcement against corporations committing economic crimes are needed.